Variability of zonal currents in the eastern equatorial Indian Ocean on seasonal to interannual time scales. Issue 11 (25th November 2014) - Nyadjro, Ebenezer S.; McPhaden, Michael J.
Abstract This study examines equatorial zonal current variations in the upper layers of eastern Indian Ocean in relation to variations in the Indian Ocean Dipole (IOD). The analysis utilizes data from the Research Moored Array for African‐Asian‐Australian Monsoon Analysis and Prediction (RAMA) and the European Centre for Medium‐Range Weather Forecasts‐Ocean Reanalysis System 4 (ECMWF‐ORAS4). Surface currents are characterized by semiannual eastward flowing Wyrtki jets along the equator in boreal spring and fall, forced by westerly monsoon transition winds. The fall jet intensifies during negative IOD (NIOD) events when westerlies are anomalously strong but significantly weakens during positive IOD (PIOD) events when westerlies are anomalously weak. As zonal wind stress weakens during PIOD events, sea surface height becomes unusually low in the eastern basin and high in the west, setting up an anomalous pressure force that drives increased eastward transport in the thermocline. Opposite tendencies are evident during NIOD events in response to intensified equatorial westerlies. Current transport adjustments to anomalous zonal wind forcing during IOD events extend into the following year, consistent with the cycling of equatorial wave energy around the basin. A surface layer mass budget calculation for the eastern sea surface temperature (SST) pole of the IOD indicates upwelling of ∼2.9±0.7 Sv during normal periods, increasing by 40–50% during PIOD events and reducing effectively to zero during NIOD events. IOD‐related variations in Wyrtki jet and thermocline transports are major influences on these upwelling rates and associated water mass transformations, which vary consistently with SST changes.